The future of reproductive surgery - Noriega Hoces, Luis (2014)
It is necessary to review reproductive surgery from the perspective of in vitro fertilization (IVF) preparatory treatment. When hydrosalpinx is present, laparoscopic salpingectomy is required before entering to an IVF program, considering that surgery does not compromise ovarian stimulation or pregnancy rates with respect to patients with healthy fallopian tubes. As rates of implantation and pregnancy are not altered by endometriosis, carrying the patient to surgery risks is not worth. Faced with tubal ligation, best results are achieved when clips were applied in the middle of the isthmus and worst results when the procedure removed the distal end of the fimbria. Patients with less than 4 cm subserosal or intramural fibroids that do not alter the uterine cavity have IVF / ICSI results similar to those that do not have them, and do not require myomectomy. In cases of recurrent pregnancy loss, uterine septum and polypectomy (>9 mm), resectoscopy (by hysteroscopy) shows significant reproductive benefits. The future of reproductive surgery should consider preserving the ability to have children before considering eliminating pathology. All future trials should address the potential female fertility detrimental long-term effects.